2022
DOI: 10.1530/eje-21-0554
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal dexamethasone treatment for classic 21-hydroxylase deficiency in Europe

Abstract: Objective: To assess the current medical practice in Europe regarding prenatal dexamethasone (Pdex) treatment of CAH due to 21-hydroxylase deficiency. Design and Methods: A questionnaire was designed and distributed, including 17 questions collecting quantitative and qualitative data. Thirty-six medical centres from 14 European countries responded and 30 out of 36 centres were reference centres of the European Reference Network on Rare Endocrine Conditions, EndoERN. Results: Pdex treatment is currently provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Fetal genetic testing is usually performed around the 10th to 13th gestational week via chorionic villus sampling, but it can also be performed with amniocentesis at later times (15th to 16th gestational week) [ 16 , 50 ]. Given that genitalia formation begins around the ninth gestational week [ 51 ], starting a prenatal therapy after such time may be too late to prevent development abnormalities, posing clinicians and patients the dilemma of whether to undergo prenatal therapy, with a variable but usually substantial risk of inappropriate exposure of non-affected fetuses, or to refuse it, with subsequent risk of virilized female fetuses and related consequences.…”
Section: Cah and Pregnancymentioning
confidence: 99%
See 4 more Smart Citations
“…Fetal genetic testing is usually performed around the 10th to 13th gestational week via chorionic villus sampling, but it can also be performed with amniocentesis at later times (15th to 16th gestational week) [ 16 , 50 ]. Given that genitalia formation begins around the ninth gestational week [ 51 ], starting a prenatal therapy after such time may be too late to prevent development abnormalities, posing clinicians and patients the dilemma of whether to undergo prenatal therapy, with a variable but usually substantial risk of inappropriate exposure of non-affected fetuses, or to refuse it, with subsequent risk of virilized female fetuses and related consequences.…”
Section: Cah and Pregnancymentioning
confidence: 99%
“…Massively parallel sequencing of cell-free fetal DNA may also allow CYP21A2 genotyping, leading to an earlier diagnosis, so that non-biallelic-mutated and male fetuses may be excluded from (or less exposed to) prenatal therapy [ 49 , 51 ]. Such techniques, however, are still expensive and often unavailable: Nowotny et al reported the use of early sex typing in 11/13 tertiary care European centers and CYP21A2 genotyping in only 1/13 of these centers [ 50 ]. Nonetheless, it is foreseeable that the costs and availability of these diagnostic tests may improve over time, expanding their use, and thus improving the benefit/risk ratio of such therapy [ 53 , 54 ].…”
Section: Cah and Pregnancymentioning
confidence: 99%
See 3 more Smart Citations